Description of Poly Pharmacy Prescribed Drug Interactions on One Pharmacy at Bumi Tamalanrea Permai Makassar - Megawati, Megawati; AR., Nurul Izza; Wahdini, Wahdini (Politeknik Sandi Karsa, 2022)
Research has been carried out on the description of the interaction of prescription drugs in polypharmacy at one of the pharmacies in Bumi Tamalanrea Permai Makassar. The purpose of this study was to determine the description and number of prescription drug interactions in polypharmacy at one of the pharmacies in Bumi Tamalanrea Permai Makassar. This research was conducted descriptively and data collection was carried out prospectively. The results showed that there were 43 prescriptions (out of a total of 284 prescriptions) that had DDI potential, 5 prescriptions that had DDI potential in the major category, 11 prescriptions with moderate DDI potential, 27 recipes with minor DDI potential. The results showed that the potential for DDI that occurred was less than 50%. However, this should receive attention because DDI should not occur in drugs given to patients.